2016
DOI: 10.1021/jacs.6b00633
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Cercosporin Biosynthetic Pathway in the Fungal Plant Pathogen Cercospora nicotianae

Abstract: Perylenequinones are a class of photoactivated polyketide mycotoxins produced by fungal plant pathogens that notably produce reactive oxygen species with visible light. The best-studied perylenequinone is cercosporin-a product of the Cercospora species. While the cercosporin biosynthetic gene cluster has been described in the tobacco pathogen Cercospora nicotianae, little is known of the metabolite's biosynthesis. Furthermore, in vitro investigations of the polyketide synthase central to cercosporin biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 59 publications
(137 reference statements)
8
87
0
Order By: Relevance
“…the sources of HA substrates, and the genes marked with red on the right were upregulated in the transcriptome analysis we performed (Zhao et al, 2016). The proposed functions of the proteins encoded by the HA biosynthesis gene cluster are based on the biosynthesis studies of cercosporin (Newman and Townsend, 2016) and elsinochrome C (Chooi et al, 2017). The orange dotted lines represent the substrates for HA biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the sources of HA substrates, and the genes marked with red on the right were upregulated in the transcriptome analysis we performed (Zhao et al, 2016). The proposed functions of the proteins encoded by the HA biosynthesis gene cluster are based on the biosynthesis studies of cercosporin (Newman and Townsend, 2016) and elsinochrome C (Chooi et al, 2017). The orange dotted lines represent the substrates for HA biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the CTB and HA cluster genes, NADPH-dependent oxidoreductase (CTB6) and FAD-dependent monooxygenase (CTB7) appeared to be unique to the CTB cluster. Considering the function of these enzymes, it makes sense that they are absent in the HA cluster, given that these structural features are non-existent (Newman and Townsend, 2016). Future studies are needed to determine whether these genes participate in HA biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…A biosynthetic pathway for cercosporin was also proposed (Chen et al, 2007). However, recent studies presented alternative biosynthetic pathways obtained by the characterization of metabolites from a series of biosynthetic pathway gene knockouts, as well as the discovery of several additional genes required for cercosporin biosynthesis through a comparative genomic and conserved gene cluster analysis (de Jonge et al, 2017(de Jonge et al, , 2018Newman and Townsend, 2016;Shim and Dunkle, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of assessed species from the genus Colletotrichum , a large genus of crop and/or ornamental plant pathogens (Perfect et al, ), were shown to harbour full‐ to partial‐length CTB gene clusters, of which the post‐harvest apple fruit pathogen Co. fioriniae was shown to produce cercosporin (de Jonge et al, ). The core gene of the Cercospora CTB gene cluster is the NR‐PKS gene CTB1 (Newman and Townsend, ), which is flanked by nine genes that encode decorating enzymes (CTB2, CTB3, CTB5, CTB6, CTB7, CTB9, CTB10, CTB11 and CTB12) (de Jonge et al, ). Besides those 10 genes essential for toxin formation, the cluster also encodes a zinc finger transcription factor (CTB8) for regulation of cluster gene expression, and two major facilitator superfamily (MFS) transporters; CTB4 that is necessary for toxin secretion and the cercosporin facilitator protein (CFP) involved in toxin auto‐resistance (Chen et al, ; Choquer et al, ; de Jonge et al, ).…”
Section: Introductionmentioning
confidence: 99%